Pengaruh Pendidikan Kesehatan Tentang Iva Dan Pap-Smear Terhadap Tingkat Pengetahuan Dan Sikap Wus Melalui Media Leaflet Berkalender Dalam Upaya Deteksi Dini Kanker Serviks Di Wilayah Kerja Puskesmas Manahan Kota Surakarta - Rahmawati, Chusniah Windi, Yuli Kusumawati, S.KM, M.Kes (Epid) (2016)
Cervical cancer inhabitant high risk of Indonesia on 20 until 50 years old. Cervical cancer can be cure if earlier to detection, it can be done by the visual inspection with acetic acid (VIA) and Pap-smear. Roud up of VIAand Pap-smear examination is low (1,75%) because less knowledge. Health Education is the one of efforts for increasing the knowledge.The purpose of this research to know the effect of healt education about VIA and Pap-smear with calendar leaflet on knowledge and attitude of women in Puskesmas Manahan administration area of Surakarta. The study design is quasi eksperimental design with pre-test post-test with control group. The population in this research are all women and live in Puskesmas Manahan administration area. Selected sample with simple random sampling and obtained sample 65 people of exsperimen group and 65 people of control group.The data analysis with paired t-test and independent t-test, data was analized by using SPSS 20 program. Result research showed that was difference of score before and after given health education for women level of knowledge and attitude (p=0,000) and was difference effect of health education use ceramah method + calendared leaflet with ceramah method only to knowledge and attitude women (p<0,05).